2013
DOI: 10.4049/jimmunol.1202862
|View full text |Cite
|
Sign up to set email alerts
|

Troxerutin Counteracts Domoic Acid–Induced Memory Deficits in Mice by Inhibiting CCAAT/Enhancer Binding Protein β–Mediated Inflammatory Response and Oxidative Stress

Abstract: The C/EBP β is a basic leucine zipper transcription factor that regulates a variety of biological processes, including metabolism, cell proliferation and differentiation, and immune response. Recent findings show that C/EBP β–induced inflammatory responses mediate kainic acid–triggered excitotoxic brain injury. In this article, we show that protein kinase C ζ enhances K-ras expression and subsequently activates the Raf/MEK/ERK1/2 pathway in the hippocampus of domoic acid (DA)–treated mice, which promotes C/EBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 50 publications
5
53
0
1
Order By: Relevance
“…These results could be extended to cellular systems, implicating the antioxidant potential of TRX. Our results strengthen the reports by many other investigators including those from our laboratory, that it can be utilized to minimize oxidative stress-induced damage to biological systems (Adam et al, 2005;Fan et al, 2009;Zhang et al, 2009;Lu et al, 2013). These results also explain the ability of TRX to ameliorate radiation -induced damage both in vitro and in vivo model systems, as ionizing radiation elicits toxic effects mainly through generation of free radicals (Maurya et al, 2004;Ping et al, 2012).…”
Section: Mitochondria and In Cells In Vitrosupporting
confidence: 93%
See 1 more Smart Citation
“…These results could be extended to cellular systems, implicating the antioxidant potential of TRX. Our results strengthen the reports by many other investigators including those from our laboratory, that it can be utilized to minimize oxidative stress-induced damage to biological systems (Adam et al, 2005;Fan et al, 2009;Zhang et al, 2009;Lu et al, 2013). These results also explain the ability of TRX to ameliorate radiation -induced damage both in vitro and in vivo model systems, as ionizing radiation elicits toxic effects mainly through generation of free radicals (Maurya et al, 2004;Ping et al, 2012).…”
Section: Mitochondria and In Cells In Vitrosupporting
confidence: 93%
“…It has also been previously reported to have antioxidant effects in different tissues, e.g. liver, kidney and brain ( Adam et al, 2005;Fan et al, 2009;Zhang et al, 2009;Lu et al, 2013). Studies by Ping, Junqing, Junfeng & Enjin (2012) have demonstrated that prior administration of 10 mg per kg of TRX to mice offered 70% protection against whole body γ-irradiation-induced mortality.…”
Section: Discussionmentioning
confidence: 89%
“…Troxerutin also has been reported to block the endoplasmic reticulum stress and oxidative stress pathway in brain and liver of mice [18, 42, 43], and troxerutin could increase the activity of anti-oxidant enzymes and limiting the lipid peroxidation [44]. We need to do further study to explore if these pathways also participate the protective effect of troxerutin in myocardial I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated other beneficial effects of troxerutin, in vitro and in vivo, and it may be effective in reducing different cytotoxicities. In particular, troxerutin has been observed to exhibit an inhibitory effect on the neurotoxicity induced by high cholesterol-mediated cognitive deficits, kainic acid-triggered excitotoxic damage and β-amyloid oligomerization (3)(4)(5). In addition, troxerutin has a photoprotective effect against ultraviolet B (UVB) radiation in human skin cells, including dermal fibroblasts and keratinocytes (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo investigations have demonstrated that CVI-bearing patients have increased levels of ROS, and troxerutin has a protective effect against oxygen-derived free radical scavengers on the endothelium in these patients (10,11). In addition, the aforementioned neurotoxicities are inhibited following troxerutin application by reducing the production of ROS (3,4,12). UVB and γ-radiation are known ROS stimulators (13,14), and a previous study demonstrated that troxerutin protects against radiation-induced lipid peroxidation (9).…”
Section: Introductionmentioning
confidence: 99%